sin5°-sin67°+sin77°-sin139°+sin149°=0
Answers
LHS = sin5° - sin67° + sin77° - sin139° + sin149°
we know, sinA - sinB = 2cos(A + B)/2.sin(A - B)/2
so, -sin67° +sin77° = 2cos(67°+77°)/2.sin(77° - 67°)/2
= 2cos72° . sin5°
similarly, -sin139° . sin149° = 2cos(139°+149°)/2.sin(149° - 139°)/2
= 2cos(144°).sin5°
now, LHS = sin5° + 2cos72°sin5° + 2cos144°.sin5°
= sin5° [ 1 + 2cos72° + 2cos144°]
= sin5°[1 + 2(cos72° + cos144°)]
we know, cosA + cosD = 2cos(C + D)/2.cos(C - D)/2
= sin5° [ 1 + 2{2cos(72°+144°)/2.cos(144°-72°)/2]
= sin5° [1 + 4cos108°.cos36°]
= sin5° [1 + 4cos(90° +18°) .cos36°]
= sin5° [ 1 - 4sin18°.cos36° ]
[ cos36° = (√5 + 1)/4 and sin18° = (√5 - 1)/4
so, sin18°.cos36° = (√5² - 1²)/16 = 4/16 = 1/4 ]
= sin5° [1 - 4 × 1/4 ]
= sin5° [1 - 1]
= 0 = RHS
also read similar questions :show that: cos 2theta cos theta/2-cos3theta cos9theta /2= sin5 theta son 5 theta /2
https://brainly.in/question/5910427
prove that sin theta/2× sin 7 theta/2 + sin 3 theta/2× sin 11 theta/2 = sin2 theta× sin5 theta
https://brainly.in/question/4998243